PENGARUH ZAKAT TERHADAP PENGURANGAN KEMISKINAN DI INDONESIA PERIODE 2015 - 2023 - Sarah Fitria Harahap; Yenni Samri Juliati Nasution (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
The purpose of this study is to determine the effect of zakat on poverty reduction in Indonesia. This study uses one dependent variable, namely poverty and one independent variable, zakat. The research method used is a quantitative method with a simple linear regression model. The data source used is secondary data obtained from the official BPS website, namely www.bps.go.id and BAZNAN www.baznas.go.id. Data analysis techniques use classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests), T statistical tests, and linear regression tests. The results of this study indicate that zakat has a significant effect and has a negative effect on poverty in Indonesia, where zakat has an effect of 31.36% on poverty in Indonesia while the remaining 68.64% is explained by variables outside the model